CRIME, FEAR, AND MENTAL HEALTH IN MEXICO1. Issue 4 (1st November 2017) - VILLARREAL, ANDRÉS; YU, WEI‐HSIN
Abstract: This article examines the effect of exposure to criminal violence on fear of crime and mental health in Mexico, a country that has experienced a dramatic rise in violent events resulting from the operation of drug trafficking organizations (DTOs). Data are drawn from more than 30, 000 respondents to a national longitudinal survey of Mexican households. We use fixed‐effects models which allow us to control for time‐invariant individual and municipal characteristics affecting both exposure to violence and mental health. The results indicate a substantial increase in fear and psychological distress for individuals living in communities that suffered a rise in the local homicide rate even when exposure to other forms of victimization and more personal experiences with crime are taken into account. Because DTO killings occur in response to factors external to a specific neighborhood, they generate fear and psychological distress at a larger geographical scale. They also seem to create a generalized sense of insecurity, leading to increased fear of other types of crimes. We examine the effect of large surges in homicide and the presence of military and paramilitary groups combatting DTOs as these conditions may approximate those in conflict zones elsewhere in the world. We also explore differences in the relative sensitivity to homicide rates between sociodemographic groups.